PENINGKATAN KUALITAS TAHSIN IBU-IBU DAN ANAK-ANAK MELALUI HALAQOH METODE TALAQQI DI MUSHOLLA AT-TAQWA: PENINGKATAN KUALITAS TAHSIN IBU-IBU DAN ANAK-ANAK MELALUI HALAQOH METODE TALAQQI DI MUSHOLLA AT-TAQWA - Bahrul Ulum; Khairul Anhar; Teguh Samta Adrian; Muhammad Zaid Rusdi; Muhammad Ridha; Albahroyni (As-sunnah: Jurnal Pengabdian Masyarakat, 2026)
The core problem addressed in this community service was the low quality of Qur'anic recitation among mothers and children in Aliantan Village, marked by inaccurate makharijul huruf and inconsistent application of mad rules. The activity was carried out atMusholla At-Taqwa, Aliantan Village, Rokan Hulu Regency, involving the MushollaProsperity Board (BKM) and local community leaders as principal partners. Participatory Action Research (PAR) served as the methodological framework, operationalized through cycles of initial observation, program planning, field action, and continuous reflection. The team applied intensive talaqqi and musyafahah techniques within small halaqahgroups so that each participant received individual correction. Twelve days of intervention with forty active participants (n = 40) generated measurable improvements in technical reading ability. The mothers' group (n = 10) showed a rise in the accuracy of mad thabi'i from twenty percent to eighty percent, while the children's group (n = 30) demonstrated rapid progress in articulating difficult letters such as 'ain and qaftogether with stronger comprehension of basic worship. Beyond cognitive and psychomotor gains, the program strengthened ukhuwah between the KKN-T students and villagers through collaborative activities including mutual work and communal iftar. The halaqahsystem proved effective for mapping heterogeneous entry levels, so that recitation improvement became more focused, intensive, and well documented.